Assessing the Impact of PCSK9 and HMGCR Inhibition on Liver Function: Drug-Target Mendelian Randomization Analyses in Four AncestriesSummary - Daniel B. Rosoff; Andrew S. Bell; Josephin Wagner; Lucas A. Mavromatis; Ali Hamandi; Lauren Park; Jeesun Jung; Falk W. Lohoff (Cellular and Molecular Gastroenterology and Hepatology, 2024)
Background & Aims: Observational studies have linked lipid-lowering drug targets pro-protein convertase subtilisin/kexin 9 (PCSK9) and HMG-CoA reductase (HMGCR) with adverse liver outcomes; however, liver disease incidence varies across diverse populations, and the long-term hepatic impact of these lipid-lowering drugs among non-white Europeans remains largely unknown. Methods: We use single nucleotide polymorphisms (SNPs) in PCSK9 and HMGCR loci from genome-wide association study data of low-density lipoprotein cholesterol in 4 populations (East Asian [EAS], South Asian [SAS], African [AFR], and European [EUR]) to perform drug-target Mendelian randomization investigating relationships between PCSK9 and HMGCR inhibition and alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), and bilirubin. Results: Analyses of PCSK9 instruments, including functional variants R46L and E670G, failed to find evidence for relationships of low-density lipoprotein cholesterol lowering via PCSK9 variants and adverse effects on ALT, AST, GGT, or ALP among the cohorts. PCSK9 inhibition was associated with increased direct bilirubin levels in EUR (β = 0.089; P value = 5.69 × 10–6) and, nominally, in AFR (β = 0.181; P value = .044). HMGCR inhibition was associated with reduced AST in SAS (β = –0.705; P value = .005) and, nominally, reduced AST in EAS (β = –0.096; P value = .03), reduced ALP in EUR (β = –2.078; P value = .014), and increased direct bilirubin in EUR (β = 0.071; P value = .032). Sensitivity analyses using genetic instruments derived from circulating PCSK9 protein levels, tissue-specific PCSK9 expression, and HMGCR expression were in alignment, strengthening causal inference. Conclusions: We did not find ALT, AST, GGT, or ALP associated with genetically proxied PCSK9 and HMGCR inhibition across ancestries. We identified possible relationships in several ancestries between PCSK9 and increased direct and total bilirubin and between HMGCR and reduced AST. These findings support long-term safety profiles and low hepatotoxic risk of PCSK9 and HMGCR inhibition in diverse populations.